Grid-connected photovoltaic-based microgrid as charging infrastructure for meeting electric vehicle load - Chowdary, Appalanaidu; Rao, Sura Srinivasa (Frontiers in Energy Research, 2022)
Concerns about charging Infrastructure have arisen as electric vehicles (EVs) gain popularity in the transportation sector. Like gas stations, the charging infrastructure is mainly used to power the EV batteries until they are fully charged. As a result, many alternative options for creating charging stations were explored in the literature. This study proposes a grid-connected photovoltaic-based microgrid for EV charging infrastructure. It has two objectives: to design and model a grid-connected photovoltaic-based microgrid and to analyze a hypothetical EV population charging. While modeling, the realistic EV loads are considered, and the simulation is carried out. Results of this study include the power generation potential from the solar power plant, the energy mix of the microgrid (i.e., grid shared energy and onsite solar generation), and supply and load mismatch relationships. The analysis results include the weather parameter influence on power produced, followed by sensitivity analysis quantifying the impact of scaled EV sessions over microgrid power balances. Overall, it is understood that grid-connected microgrids support the seamless charging of EVs even in the case of uncertainties observed with onsite solar energy generation.